Development of quality criteria for supplier selection - Sadigh, Aghdas Naimi (2009)
In supply chain management, supplier selection is one of the most important components of production and logistics management for many companies. Selecting the right suppliers based on high quality and reliability will significantly reduce purchasing costs and other costs related to purchasing indirectly. Consequently, the selection of a wrong supplier could be enough to upset the companies' functional and operational position. There are many criteria III order to assess supplier such as quality, delivery, performance and price. Quality is the ongoing process of producing and sustaining relationship by assessing, anticipating and fulfilling stated and implied needs. The methods for assessing the quality of products for suppliers can be divided to qualitative methods such as continuous improvement programs, certifications, technical and design level, and quality for customer and quantitative methods such as yield rate, process capability indices, reliability and rate of rejects. Since each method can evaluate just one aspect of an organization and cannot evaluate the whole production process, they are not suitable to assess the product's quality of supplier selection process. Therefore to address this problem, this study aims to define a real cost-based objective function for assessing suppliers. In order to form the objective function of the model, three main criteria, quality, price and transportation cost were selected. In this method each of quality costs, price and transportation costs were used as parameters. Revised Taguchi loss function was used to assess the quality of products whereas were used a simple linear programming (LP) model and SOLVER software were used to determine the parameters. There are other loss functions such as inverted normal loss function, asymmetric inverted normal loss function, and revised inverted normal loss function. The concepts of them are the same and based on loss, but their formulas and applications are different. This model was also developed by other loss functions. Data were taken from an Iranian Plastic Company and proved that it is workable and beneficial. Finally, a sensitivity analysis was conducted in order to compare the usage of different loss functions. The proposed model has some advantages such as simpler operations research model, integration of quality cost, purchasing cost and transportation cost and better estimation of quality compared with old methods such as rate of rejects.